2014
DOI: 10.2460/javma.244.9.1037
|View full text |Cite
|
Sign up to set email alerts
|

Pathology in Practice

Abstract: HistoryAn approximately 10-month-old female Syrian hamster (Mesocricetus auratus) was submitted for necropsy. The pet had died following a 6-week period of weight loss, lethargy, and tachypnea with increased abdominal effort. The hamster was previously evaluated by a veterinary ophthalmologist because of several small nodules on both lower eyelids at the medial canthus; on the basis of the physical examination findings, these nodules were diagnosed as cysts.On external examination of the hamster, there were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…HaPyV may induce T-cell and B-cell lymphomas. 4,5,15 A previous study on the HaPyV pandemic in a colony of GASH: Sal Syrian hamsters reported a high incidence of non-Hodgkin, Burkitt-type B-cell lymphoma in affected hamsters. 20 HaPyVassociated lymphomas in the abdominal cavity have been suggested to possess the B-cell immunophenotype, while those in the thymus possess the T-cell immunophenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HaPyV may induce T-cell and B-cell lymphomas. 4,5,15 A previous study on the HaPyV pandemic in a colony of GASH: Sal Syrian hamsters reported a high incidence of non-Hodgkin, Burkitt-type B-cell lymphoma in affected hamsters. 20 HaPyVassociated lymphomas in the abdominal cavity have been suggested to possess the B-cell immunophenotype, while those in the thymus possess the T-cell immunophenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of HaPyV infection have been reported in the United States and Europe. 5,11,20,27 There are 3 main outcomes of HaPyV infection: subclinical effects, trichoepithelioma, and lymphoma. 4,15,26 HaPyV infection in older hamsters is typically subclinical and the virus persists in the renal tubular epithelium, resulting in continued viruria.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The tumors appeared spontaneously in young animals of about 3 months to more than one year of age. Polyomavirus infections in hamsters were also reported from the United States (Newfield, NJ [ 16 ]; Columbia, MO [ 17 ]; New Haven, CT [ 18 ]) and Europe (Bristol, GB [ 19 ]; Salamanca, Spain [ 20 ]). In general, HaPyV infections are rarely reported.…”
Section: Hamster Polyomavirus—its Discovery and Initial Characterizationmentioning
confidence: 99%
“…The invasion of adjacent tissue and metastasis occur often. The concurrent formation of skin tumors and lymphoma in a hamster individuum is a relatively rare event [ 18 ].…”
Section: Hapyv As Pathogenmentioning
confidence: 99%